2021
DOI: 10.1021/acsaelm.1c00267
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review on Flexoelectric Energy Harvesting Technology: Mechanisms, Device Configurations, and Potential Applications

Abstract: Flexoelectricity is the electromechanical coupling between mechanical strain gradient and electric polarization or vice versa. This unique effect becomes considerable as the material dimension decreases and is found in a wide range of materials. In this review, flexoelectric effects in different dielectric materials and their characterization methods have been summarized. Also, the different mechanical structures for the measurement of electric outputs corresponding to different components of strain gradient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 149 publications
0
17
0
Order By: Relevance
“…Continuously, upon application of completely external pressure, vertical strain gradients occur within the multilayered MoS 2 spheres owing to the stacked sphere structure. The strain gradient, as shown in the following eq , is proportional to the electric polarization induced by the flexoelectric effect where P l is the induced flexoelectric polarization, S ij is the elastic strain, μ ijkl is the flexoelectric coefficient, and x k is the position coordinate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuously, upon application of completely external pressure, vertical strain gradients occur within the multilayered MoS 2 spheres owing to the stacked sphere structure. The strain gradient, as shown in the following eq , is proportional to the electric polarization induced by the flexoelectric effect where P l is the induced flexoelectric polarization, S ij is the elastic strain, μ ijkl is the flexoelectric coefficient, and x k is the position coordinate.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Therefore, unlike the piezoelectric effect, the electric polarization of the flexoelectric effect can be improved by maximizing the strain/stress gradient based on the control of various nano-or microscale materials and devices, which can be applied to all-dielectric materials to effectively generate electrical signals from mechanical stimuli. 30,31 Recently, many researchers have been interested in flexoelectric devices and the operating mechanism. For instance, Kim et al reported flexoelectric-boosted electromechanical properties of piezoelectric nanoparticles using an induced built-in strain gradient in a heterogeneous core− sphere nanostructure of BaTiO 3 @SrTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small scale mechanical motion, including human or animal motion, vibrations and acoustic waves, are of great importance for powering wearable, implantable, and remote microelectronics. [ 1 ] Electromechanical energy harvesters, including piezoelectric, [ 2 ] triboelectric, [ 3 ] and flexoelectric devices, [ 4 ] are able to capture this mechanical energy and generate electricity. Of these, only triboelectric devices are able to be produced from a wide range of generally available materials.…”
Section: Introductionmentioning
confidence: 99%
“…The precise flexoelectric coefficients will be equally significant from basic concepts and application viewpoints. The uncertainty in flexoelectric coefficients will enormously affect the accuracy of devices because they act as input parameters in developing flexoelectric-based devices such as flexoelectric-energy-harvesters [18], sensors [19], and actuators [20]. Therefore, various experimental designs, such as threeand four-point bending [21,22], pyramid compression [23], shock wave [24], and converse flexoelectric method [25], are proposed for measuring the pure flexoelectric coefficients.…”
Section: Introductionmentioning
confidence: 99%